6,7-Disubstituted-4-anilinoquinazoline: Design, Synthesis and Anticancer Activity as a Novel Series of Potent Anticancer Agents - Fatemeh Azmian Moghadam; Mehdi Evazalipour; Hassan Kefayati; Saeed Ghasemi (Tabriz University of Medical Sciences, 2021)
Background: Epidermal Growth Factor Receptor (EGFR) and vascular endothelial growth factor receptor (VEGFR) are responsible for several pathological conditions such as the development of different kinds of tumors. The combined inhibition of both signal transduction pathways seems to be a promising novel approach for cancer treatment. Methods: In this study, novel 4-anilinoquinazoline derivatives with various substituents on-7 position of quinazoline moiety were designed, synthesized, and evaluated for their antiproliferative activity against A431 and HU02 cell lines. Results: Compounds 8a, 8d, and 8f displayed the most potent anticancer activities against A431(IC50 = 1.78 μM, 8.25 μM, and 7.18 μM, respectively) in comparison with reference standards(erlotinib IC50=8.31 μM and vandetanib IC50=10.62 μM). Molecular docking studies proved that8a as the most potent compound could be efficiently accommodated in the ATP binding site ofEGFR and VEGFR-2 through the formation of essential hydrogen bonds between quinazolineN1 atom and the Met796 backbone of EGFR as well as the Cys919 backbone of VEGFR-2 with a distance of 1.94 Å and 1.398 Å, respectively. Conclusion: Compound 8a as the most potent compound with morpholine and 3-bromoaniline at the 7 and 4 positions of quinazoline scaffold, respectively, deserves more study and structural optimization as an anticancer agent.